Association between delirium and statin use in patients with congestive heart failure: a retrospective propensity score-weighted analysis - Xia, Jiangling; Wang, Leilei; Zhang, Nannan; Xu, Hongyu (Frontiers in Aging Neuroscience, 2023)
Abstract Background: Clinical effects of statins in delirium still provoke debate. We aimed to assess the association between statins exposure and delirium and in-hospital mortality in patients with congestive heart failure(CHF). Methods: In this retrospective cohort study, CHF patients were identified from the Medical Information Mart for Intensive Care (MIMIC-IV) database.The primary exposure variable was statins use three days before intensive care unit (ICU) and the primary endpoint was the presence of delirium. The secondary endpoint was in-hospital mortality As the cohort was nonrandom, inverse probability weighting (IPW) derived from propensity scores was used to reduce imbalances of characteristics. Results: Among a population of 8396 patients, 5446 (65%) were exposed to statins use. Before matching, the prevalence of delirium was12.5% and in-hospital mortality 11.8% for patients exposed to statins.Exposure to statins was estimated to be significantly associated with delirium by a factor of 0.73 (95% CI, (0.64~0.84); P < 0.001) in the IPW cohort and with in-hospital mortality by a factor of 0.74 (95% CI, 0.62 (0.55~0.71) P < 0.001). Conclusion: Statin use was significantly associated with a decreased incidence of delirium and in-hospital mortality in patients with CHF.